If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-19=-7x+6x-9
We simplify the equation to the form, which is simple to understand
-19=-7x+6x-9
We move all terms containing x to the left and all other terms to the right.
+7x-6x=-9+19
We simplify left and right side of the equation.
+1x=+10
We divide both sides of the equation by 1 to get x.
x=10
| 42+2x=7x+18 | | 10x+3=7x+9 | | X^2+4x^2=20 | | 3x+4+3x=-50 | | 9.4=x-15 | | 3x+15=47-3x | | 10X+6=96 | | 3x+5=25 | | 170-7x=38x+20 | | 5(x+17)=3x+6 | | 10X-9=51 | | -6x+1=-47 | | 7-8x=39-15x | | 10X+4=54 | | 8x^2+-70x+-750=0 | | 3x+5=(x+1)*3+2 | | -2x^2+8x+15=0 | | 4x(x-3)=9(x-7) | | 10-8x=88-29x | | 6x+35=13x-21 | | 3q=100-10q+10+2q | | x^2-3x-130=0 | | 122-4x=5x+14 | | h^2=c^2+c^2 | | x-(x(.05))=100 | | 61-3x=1x+22 | | 5x-17=3(x+6) | | 3(2q-7)-(3q-8)+22=0 | | -6(2n+3)= | | -40-2x=10-7x | | 60-6x=3x+19 | | 8x-14=3x+1x |